The Protein Paradox: Elucidating the Complex Nutritional Ecology of the Invasive Berry Pest, Spotted-Wing Drosophila (Diptera: Drosophila suzukii) - Deans, Carrie; Hutchison, William D. (Frontiers in Insect Science, 2021)
Spotted-wing drosophila (SWD), Drosophila suzukii, has become one of the most widely studied insect species over the last decade, largely due to its recent invasion and rapid expansion across the Americas and Europe. Unlike other drosophilid species, which colonize rotting fruit, SWD females possess a serrated ovipositor that allows them to lay eggs in intact ripening fruit, causing significant economic problems for fruit/berry producers worldwide. Though an impressive amount of research has been conducted on SWD's ecology and physiology, aspects of their nutritional ecology remain ambiguous. This review synthesizes the research to date to provide a more comprehensive view of SWD's nutritional relationship with its fruit hosts and associated microbes. Overall, data suggest that SWD's ability to utilize novel resources is likely due to changes in their ecological, rather than physiological, niche that are largely mediated by microbial associations. Studies show that SWD's nutrient intake is comparable to other drosophilid species, indicating limited adaptation to feeding on lower-protein resources. Instead, data show that fruit protein content is a reliable predictor of host suitability and that fruit-microbe dynamics have a strong impact on protein availability. In particularly, fruit protein increases after infestation with SWD-associated microbes, suggesting that initially-suboptimal intact fruits can become protein-rich on a timeframe that is relevant for larval nutrition. This body of work suggests that microbial associations between flies and their fruit hosts can compensate for the nutritional differences between intact and rotting fruit, and that these relationships are likely responsible for SWD's expanded nutritional niche.